On the taxonomy of freshwater crabs allied to the genus Potamon (Potamidae) in Vietnam - Thanh, Dang Ngoc; Hai, Ho Thanh (Academia Journal of Biology, 2014)
On the taxonomy of freshwater crabs allied to the genus Potamon (Potamidae) in Vietnam